Strategic management insights from a SWOT perspective: developing tourism villages in Subang District, West Java, Indonesia - Dasril Indra; Endang Sinaga; Samad Chakour; Anwari Masatip (Journal of Applied Sciences in Travel and Hospitality, 2025)
The research provides strategic management insights by applying a SWOT analysis framework to develop Subang District, West Java, Indonesia tourism villages. It focuses on formulating an effective management and development strategy for Sari Bunihayu Tourism Village, one of the region’s earliest tourism sites. Developing tourism villages in Indonesia is a strategic effort to strengthen rural economies, preserve cultural identity, and promote sustainable tourism. Despite its strong tourism potential, Sari Bunihayu faces key challenges, including weak institutional governance, underdeveloped infrastructure, limited digital promotion, and fragmented stakeholder coordination. Using a mixed-method research design, the research integrates qualitative approaches, field observations, document analysis, and stakeholder interviews, with quantitative techniques involving weighted SWOT matrices validated by expert input. Findings show that Sari Bunihayu falls within Quadrant II of the SWOT matrix, indicating that internal strengths can be utilized to address external threats. Strategic priorities include enhancing community participation, preserving traditional knowledge, and strengthening destination branding to support cultural and agrotourism. Recommended initiatives involve developing educational tourism programs, hosting annual cultural festivals, improving digital marketing led by local youth, and forming a tourism cooperative to reinforce institutional capacity. The research recommends stronger collaboration among communities, government, academia, and the private sector. It also highlights the need for improved infrastructure, human capital development, and policy integration to ensure inclusive, adaptive, and sustainable tourism governance. Ultimately, this research presents a replicable strategy model for rural tourism development in Subang Regency, supporting broader equity, sustainability, and cultural preservation goals.